"How do I survive exclusion?" Voices of students with disabilities at China's top universities. (January 2021) - Li, Huan; Lin, Jiaying; Wu, Hongyu; Li, Zhaojun; Han, Mengxue
Highlights: Students with disabilities experienced both intentional and unintentional exclusion. Students with disabilities tended to apply more positive solution strategies than negative avoidance strategies in coping with exclusion. Students with disabilities applied self-adjustment strategies to shift negative strategies into positive ones. Abstract: While researchers continue to work on experiences of exclusion among students with disabilities (SWD) in higher education, the dimensions of such experiences among SWD remain inconsistent across culturally diversified studies, and related research with a focus on China has been absent. Furthermore, little is known about the coping strategies of SWD facing exclusion. To address these research gaps, this study explores experiences of exclusion and coping strategies among SWD at China's top universities, using a qualitative research approach. Individual online interviews were conducted with 13 SWD at China's top universities. Our findings suggest that SWD in China experience not only some forms of intentional exclusion but also some forms of unintentional exclusion. Specifically, four dimensions of exclusion are identified: 1) reduction or deprivation of opportunities; 2) unequal participation; 3) limited or unequal access to resources; and 4) marginalization of interpersonal relationships. In terms of coping strategies, SWD tend to adopt more positive solution strategies (i.e., support seeking and problem solving) than negative avoidance strategies (i.e., distancing and internalizing) when facing exclusion, and some SWD apply self-adjustment strategies to change their negative strategies into positive ones. Implications for future research and practice in inclusive higher education are discussed.